2020
DOI: 10.5114/pq.2020.95771
|View full text |Cite
|
Sign up to set email alerts
|

Change in the biomechanical characteristics of running as a result of an individual 1-year program for training an elite athlete with visual impairment for Paralympic Games

Abstract: Introduction. To identify the effectiveness of an individual track and field sprint training program for an elite athlete with visual impairment to improve running techniques and increase competitive performance. Methods. An elite athlete, a Paralympic medallist and winner in the 2016 World Championship of Athletes with disabilities was involved in the study. An individual training program was developed, based on improving speed endurance and the kinaesthetic analyser. The biomechanical indicators of running w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The statistically significant results concerning ankle stability index, along with no occurrence of lower limb injuries during the competitive season, indicates that targeted sport-specific proprioceptive exercises should be incorporated in blind baseball athletic training. In agreement with the aforementioned findings, it has been previously reported that stabilization and balance exercises performed on unstable supports significantly improve kinesthetic analyzer development leading to an increase in reactivity, neuromuscular coordination, and functional joint work [ 46 ]. There is also evidence to indicate that weak ankle flexor muscles or limited loaded dorsiflexion deeply affect dynamic balance, and hence, represents the major leading cause of falls and ankle sprain [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The statistically significant results concerning ankle stability index, along with no occurrence of lower limb injuries during the competitive season, indicates that targeted sport-specific proprioceptive exercises should be incorporated in blind baseball athletic training. In agreement with the aforementioned findings, it has been previously reported that stabilization and balance exercises performed on unstable supports significantly improve kinesthetic analyzer development leading to an increase in reactivity, neuromuscular coordination, and functional joint work [ 46 ]. There is also evidence to indicate that weak ankle flexor muscles or limited loaded dorsiflexion deeply affect dynamic balance, and hence, represents the major leading cause of falls and ankle sprain [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, since hearing is confined to the head level and plays a role in postural adjustments in cases of vision loss, such athletes tend to lean their trunk forward to maximize auditory input from their feet during running [ 44 ], which negatively affects balance and speed [ 45 ]. Therefore, athletic trainers managing visually impaired competitive players should always carefully consider not only their anatomo-functional characteristics, but also their disability-related compensatory strategies to increase sport-specific performance and prevent injuries [ 46 ]. On this basis, the ankle stability and postural control were investigated using a quantitative tool such as Libra Easytech that allowed us to simultaneously obtain anatomic, functional, and sensorimotor parameter-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of visual input during sprinting can reduce horizontal sprint speed. By incorporating kinesthetic training (exercises with unstable supports), improvements to neuromuscular control of lower limbs and trunk stability may be an important factor in improving kinesthetic awareness [ 34 ] and subsequent sprint speed. Therefore, practitioners working with athletes with a visual impairment should incorporate physical assessments of postural and gait imbalances, incorporate stability and proprioceptive training in sport-specific positions, and implement strength programs focused on maximizing horizontal sprinting velocity.…”
Section: Standingmentioning
confidence: 99%